Asymmetric Dimethylarginine (ADMA) level in Serum of Preeclamptic patients - Al-Rubaye, Faisal Gh. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Preeclampsia, the de novo occurrence of hypertension and proteinuria after the 20th week of gestation, continues to exert an inordinate toll on mothers and children alike.The idea that asymmetric dimethylarginine (ADMA) accumulation may be a cardiovascular risk factor in patients with preeclampsia was advanced in 2003. Furthermore, High ADMA levels have been associated with alterations in the regulation of cerebral blood flow and neural function, with insulin resistance, thyroid dysfunction, and alterations in bone homeostasis, fertility, and erectile function.Subject and methods: the present study is a cross-sectional case-control study includes measurement of s.ADMA in 60 patients with preeclampsia. The results were compared with 60 apparently healthy pregnant women (as controls).Results: showed a significant increase in serum ADMA in the preeclamptics as compared with the controls this was accompanied by a significant reduction of this parameter with advancing gestational age in normal pregnancy.Conclusion: preeclamptics (in different gestational age groups) experienced vasospasm induced by inhibition of nitric oxide (which consider the natural vasodilator) when compared with healthy pregnant women matched with their age and gestational age; this was supported by the significant high level of s. ADMA, the endogenous inhibitor of NO .